FAKTOR-FAKTOR YANG MEMPENGARUHI PERSISTENSI LABA PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI - Grace Pratiwi; Jamaludin Iskak (Jurnal Paradigma Akuntansi, 2026)
This research was conducted to explain the effect of Accruals, Leverage, and Sales Volatility on Earnings Persistence in consumer goods manufacturing companies listed on the Indonesia Stock Exchange in 2018–2020. This research is quantitative so that the data used is secondary data obtained from financial reports. The sampling method in this study used a purposive sampling method. Samples were obtained from 22 companies during the 3 year observation period so that there were 66 samples. The IBM SPSS version 29.0 program was used in this study for data processing. The results of this study indicate that accruals have a significant effect on earnings persistence while leverage and sales volatility have no significant effect on earnings persistence.